Edukasi Tentang Pemanfaatan Kalender Menstruasi Berbasis Android Bagi Kemudahan Remaja - Nurqalbi SR; Rismawati Rismawati (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
In order to improve the community development business system so that it is more productive and efficient, technology is needed. The introduction of technology that has developed in society is technology that has been developed in a modern way, or what is known as "appropriate technology" or technology and its applications which have the characteristics of being decentralized, relatively small scale, labor intensive, energy efficient and closely related to local conditions. The socialization activity was held on Saturday, July 28 2022 at 13.00 WITA at Moncongloe Bulu Village, Moncongloe District, Kab. Maros. This activity aims to provide information to the community. To provide information to the community, especially residents of Moncongloe Village, Maros Regency, about various appropriate technologies in midwifery services and how to use appropriate technology in midwifery services, which includes how to use and utilize them. This educational process uses a lecture method with the help of powerpoints and leaflets and educational videos. The results obtained from this activity are that the mothers who participated in this service activity become more understanding and know more about how to use appropriate technology in midwifery services. The assessment is based on the participants' responses and enthusiasm in receiving the material provided. Including positive responses from participants in answering questions correctly when asked by the presenter.